Optimasi Konsentrasi Kitosan dan Lama Pengadukan dalam Preparasi Microspheres Metformin Hidroklorida (Optimization of Chitosan Consentration and Stirring Time on Preparation of Metformin Hydrochloride Microspheres) - Tintia Lintang Pratiwi; Eka Deddy Irawan; Lusia Oktora Ruma Kumala Sari (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Microspheres is multiple dosage unit controlled drug delivery system with the range of a particle size of 1-1000 µm. Chitosan was used as a polymer and metformin hydrochloride (MH) was used as a drug, and non-aqueous solvent evaporation was chosen for the techniques of microspheres preparation. MH is the first line for treatment of diabetes mellitus type 2. It has relatively low bioavailability and short half-life, therefore it is appropriate to be prepared as microspheres. Many factors affect the result of microspheres preparation, such as chitosan concentration and stirring time which used in preparation. Factorial design optimization used to determine the chitosan concentration and stirring time to produce MH-chitosan microspheres with the highest entrapment efficiency (EE). The result of microspheres preparation used 2250 mg of chitosan and 2 hours stirring time produced 81.191 % EE, and drug loading and yield of 22.673 and 89.602 %, respectively. The microspheres had spheres shape and a relatively smooth and bright surface morphology. The particle size was 653.333 μm. FT-IR analysis indicated that there were no changes in the functional groups on MH as an active ingredient. Keywords: metformin hydrochloride-chitosan microspheres, non-aquoeous solvent evaporation, factorial design, chitosan concentration, time stirring